The Effect of Communication, Information, Education on the Knowledge Level of Acceptors about Side Effects of 3-Month Contraceptive Injection at BPM L Banjaranyar Village - Safira Rizky M; Wulan Margiana (UM Purwokerto Press, 2021)
The increasing world population will cause many problems in various fields, especially in the social and economic fields. Thus, the government has taken an action by launching a family planning program to control the rate of population growth. One of the most popular family planning programs is the 3-month injection KB with side effects. This study aimed to determine the effect of the provision of communication, information, and education regarding the side effects of using a 3-month injection of KB on the level of knowledge of family planning acceptors about the side effects of using KB in BPM L in Banjaranyar village. This was comparative research with a quantitative approach. The number of samples was 15 respondents in both the intervention group and the control group. In addition, the data were collected using a questionnaire and were analyzed using the Fisher test. The result showed that there were 15 respondents (100%) in the intervention group with good predicate, while the level of knowledge in the control group with good predicate was 8 respondents (53%) and 7 respondents (40%) not good predicate. Then the P-value obtained from the Fisher test was 0.006, so the p-value was 0.05. There was an effect of the provision of communication, information, and knowledge regarding the side effects of using 3-month injectable contraceptives on the level of knowledge of family planning acceptors in BPM midwives in Banjaranyar village.